Viscosity, surface tension and droplet size of sprays of different formulations of insecticides and fungicides. (November 2017) - Carvalho, Fernando Kassis; Antuniassi, Ulisses Rocha; Chechetto, Rodolfo Glauber; Mota, Alisson Augusto Barbieri; de Jesus, Marcella Guerreiro; de Carvalho, Lídia Raquel
Abstract: The influence of three types of commercial formulation of insecticides and fungicides, emulsifiable concentrate (EC) formulation, suspension concentrate (SC) formulation and water dispersible granule (WG) formulation on the surface tension, viscosity and the droplet size spectra of sprays was evaluated using thirty commercial insecticide and fungicide products. The concentration of sprays was based on application water spray volume of 50 L ha −1 using an XR 8003VS flat fan nozzle, operated at 200 kPa pressure. The lowest surface tensions were obtained with EC formulations, while the SCs had the highest viscosities. Emulsions were the most effective at decreasing the percentage of droplets smaller than 100 μm and relative span, while increasing the DV0.1 and DV0.5 values than the dispersion-type formulations, represented by WG and SC formulations. These factors should be considered for planning spray applications and reducing drift. Highlights: Type of formulation has similar effects on droplet size distribution for spray applications of insecticide and fungicide products. A study considering a low volume application rate, relevant to current practices in Brazil, is reported. The lowest surface tensions were obtained with EC formulations, while the SCs had the highest viscosities. The EC formulations were most effective at decreasing the driftable fines than the WG and SC formulations.